Identifikasi Spesies Ikan Pelagis yang Dijual di Pasar Kota Denpasar Menggunakan Marka Control Region Mitokondria (mtDNA) - Ni Putu Dian Pertiwi (Undiksha, 2022)
Identification and inventarisation of fish species is important for fisheries data. Information regarding fish species sold within the local markets of Denpasar city-Bali have not been collected and written as a good data, especially identification using molecular methods and comparison between local name and species name. Therefore, this study aims to identify species of pelagic fish sold within markets of Denpasar city using control region mitochondrial (mtDNA) marker. A total of 7 samples of pelagic fish were collected from 2 markets within Denpasar city, in the form of full body fish, fish that has been boiled, and boiled fish body parts. DNA samples were amplified at the control region of mtDNA, and obtained the sequence length of 508-527 bp. Identification was conducted using BLAST methods and phylogenetic analysis. The result showed that the samples were identified as 4 species, i.e. Auxis rochei, Auxis thazard, Thunnus albacares, and Thunnus obesus. Through this study, we also revealed that fish with the local name “ikan tongkol” was the species of Auxis rochei, Auxis thazard, Thunnus albacares, meanwhile fish known as the local name “ikan cakalang” was the species of Thunnus obesus. The results of this study was expected to be a preliminary study about the diversity of fish sold within markets in Denpasar city, and also as the additional genetic data for pelagic fish within Bali waters. This will also act as the additional information for the methods of fish species identification.